2022
DOI: 10.3390/ijerph19010482
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women’s Exposure to Household Air Pollution in Rural Bangladesh: A Feasibility Study for Poriborton: The CHANge Trial

Abstract: The use of liquefied petroleum gas (LPG) for cooking is a strategy to reduce household air pollution (HAP) exposure and improve health. We conducted this feasibility study to evaluate personal exposure measurement methods to representatively assess reductions in HAP exposure. We enrolled 30 pregnant women to wear a MicroPEM for 24 h to assess their HAP exposure when cooking with a traditional stove (baseline) and with an LPG stove (intervention). The women wore the MicroPEM an average of 77% and 69% of the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…The findings from this study had multiple outcomes that identified issues and improved processes for conducting our trial: firstly, the development of a locally appropriate LPG cylinder supply chain in the study area, and secondly, the development of content relevant for our initial behaviour change communication such as benefits of clean cooking, practical suggestions for modifying cooking behaviours, and the important role of mothers-in-law and husbands in decision-making about cooking and fuel practices [ 30 ]. Lastly, we confirmed culturally appropriate approaches for measuring personal exposure to household air pollution and produced representative data that confirmed the LPG intervention did reduce exposure to cooking fuel emissions [ 31 ].…”
Section: Methodssupporting
confidence: 62%
“…The findings from this study had multiple outcomes that identified issues and improved processes for conducting our trial: firstly, the development of a locally appropriate LPG cylinder supply chain in the study area, and secondly, the development of content relevant for our initial behaviour change communication such as benefits of clean cooking, practical suggestions for modifying cooking behaviours, and the important role of mothers-in-law and husbands in decision-making about cooking and fuel practices [ 30 ]. Lastly, we confirmed culturally appropriate approaches for measuring personal exposure to household air pollution and produced representative data that confirmed the LPG intervention did reduce exposure to cooking fuel emissions [ 31 ].…”
Section: Methodssupporting
confidence: 62%
“…Brook et al (2010) further demonstrated that the risk of non-accidental mortality rises with chronic PM2.5 exposure. At the same time, maternity and infants are more vulnerable to air pollution compared to other age groups (Hackley et al, 2007;Thornburg et al, 2022;Wang et al, 2023). Owili et al (2017) made a similar observation regarding the significant influence of PM2.5 on maternal mortality.…”
Section: Air Pollution and Human Healthmentioning
confidence: 54%
“…As wearable technologies become more accessible, they can be used for personal monitoring and/or supplementing existing exposure assessment strategies. To date, although no studies on pregnancy loss utilize personal monitoring, studies on other health outcomes have successfully implemented this approach [48,[50][51][52][53][54]. Given pregnancy is a relatively short window of opportunity, this approach is potentially feasible and allows prospective capturing of small variation in timing, pattern, and duration of exposures, which can help explore specific windows of susceptibility.…”
Section: Exposure Assessmentmentioning
confidence: 99%